Enhancement of Solubility and Dissolution Characteristics of Ibuprofen by Solid Dispersion Technique (Dhaka University Journal of Pharmaceutical Sciences, 2012)
In this study solid dispersions (SDs) of ibuprofen were prepared by melt dispersion technique using macrogol 4000 and macrogol 6000 as carrier. Physical mixtures (PMs) of ibuprofen were also prepared with the same carrier and in the same drug-carrier ratio (1:0.5, 1:1 and 1:1.5) to compare the dissolution profile. The solid dispersions and physical mixtures were investigated for drug loading, saturation solubility and dissolution behavior. Saturation solubility study was carried out in phosphate buffer (pH 7.2), 0.1 N HCl solution and distilled water. Solid dispersions were found effective to enhance the solubility of ibuprofen significantly in all the media. Dissolution test was carried out in two different media, phosphate buffer (pH 7.2) and 0.1 N HCl. Solid dispersion containing macrogol 6000 at the ratio of 1:1.5 (drug: carrier) showed faster and higher drug release and was found to be most effective among all the solid dispersions. Drug carrier interactions were studied by comparing Fourier Transform Infrared Spectroscopy (FT-IR) of solid dispersions with pure drug which revealed that the SDs were stable. So, solid dispersion may be an effective technique to enhance dissolution rate of ibuprofen. DOI: http://dx.doi.org/10.3329/dujps.v11i1.12480 Dhaka Univ. J. Pharm. Sci. 11(1): 1-6, 2012 (June)